Preparation of Educational Materials with Integration on the Basis of Archipelagic Islam For the Intermediate Level at the Institute of Islamic Study Ma’arif Metro Lampung - Dian Risky Amalia; Bety Dwi Pratiwi (Mantiqu Tayr: Journal of Arabic Language, 2021)
This study has the objectives, 1- Preparing integrative teaching materials based on Nusantara Islam for intermediate level, 2-Knowing the characteristics of integrative teaching materials based on Nusantara Islam for intermediate level IAIM NU Metro Lampung, 3- Knowing the extent to which the effectiveness of teaching materials is to improve the four skills in Arabic.This research is an experimental research designed by researchers with pre-test and post-test. While the population of this study were second semester students majoring in English Education, and took 18 students. Results of this study are 1. Completion of teaching materials which have the following stages: Initial analysis, preparation of teaching materials, validation of 2 experts, revision of teaching materials, field trials, revision of teaching materials after implementation in the field, final results. Teaching materials compiled by researchers are in (1) Format and layout arrangements, (2) Module content consisting of instructions for use, learning and evaluation activities, (3) the use of language in teaching materials is conversational language, language of expressions / descriptions, and the natural language of the Prophet's hadith. 3. Teaching materials prepared by researchers are good and effective. This is evidenced by the result of t count (5.67) which is greater than the t table at 0.05% degree of error (2.11).